RETRACTED: The Expression of ephrinA1/ephA2 Receptor Increases in Chronic Rhinosinusitis and ephrinA1/ephA2 Signaling Affects Rhinovirus-Induced Innate Immunity in Human Sinonasal Epithelial Cells - Lee, Sang Hag; Kang, Sung Hoon; Han, Mun Soo; Kwak, Ji Won; Kim, Hyeon Geun; Lee, Tae Hoon; Lee, Da Bin; Kim, Tae Hoon (Frontiers in Immunology, 2021)
EphA2 receptor and its ephrin ligands are involved in virus infection, epithelial permeability, and chemokine secretion. We hypothesized that ephrinA1/ephA2 signaling participates in rhinovirus (RV)-induced antiviral immune response in sinonasal mucosa of patients with chronic rhinosinusitis (CRS). Therefore, we investigated the expression of ephrinA1/ephA2 in normal and inflamed sinonasal mucosa and evaluated whether they regulate chemokine secretion and the production of antiviral immune mediators including interferons (IFNs) in RV-infected human primary sinonasal epithelial cells. For this purpose, the expression and distribution of ephrinA1/ephA2 in sinonasal mucosa were evaluated with RT-qPCR, immunofluorescence, and western blot. Their roles in chemokine secretion and the production of antiviral immune mediators such as type I and III IFNs, and interferon stimulated genes were evaluated by stimulating ephA2 with ephrinA1 and inactivating ephA2 with ephA2 siRNA or inhibitor in cells exposed to RV and poly(I:C). We found that ephrinA1/ephA2 were expressed in normal mucosa and their levels increased in inflamed sinonasal mucosa of CRS patients. RV infection or poly(I:C) treatment induced chemokine secretion which were attenuated by blocking the action of ephA2 with ephA2 siRNA or inhibitor. The production of antiviral immune mediators enhanced by rhinovirus or poly (I:C) is increased by blocking ephA2 compared with that of cells stimulated by either rhinovirus or poly(I:C) alone. In addition, blocking ephA2 attenuated RV replication in cultured cells. Taken together, these results describe a novel role of ephrinA1/ephA2 signaling in antiviral innate immune response in sinonasal epithelium, suggesting their participation in RV-induced development and exacerbations of CRS.